DEVELOPMENT OF POLITICAL-DIPLOMATIC RELATIONS BETWEEN THE COUNTRIES UZBEKISTAN AND TURKEY - Имамов , Бобур (Journal of Social Sciences, 2024)
This article analyzes the formation of Uzbek-Turkish relations, the causes of political contradictions and disagreements between the two states, as well as efforts to restore these relations based on new facts,. Also in recent years, during state visits and official high-level meetings of the heads of the two states, it was noted that the signed normative legal acts in the trade, economic, scientific, technical, cultural and humanitarian spheres are becoming important for expanding bilateral mutually beneficial ties, at meetings of the heads of state of Uzbekistan and Turkey in different periods, issues on the most relevant areas of the life of the state and society. discussion, signing and implementation of agreements and agreements based on specific strategic goals are highlighted.